D2 receptor occupancy following lurasidone treatment in patients with schizophrenia or schizoaffective disorder. (30th September 2013) - Potkin, Steven G.; Keator, David B.; Kesler-West, Marilyn L.; Nguyen, Dana D.; van Erp, Theo. G. M.; Mukherjee, Jogeshwar; Shah, Nikunj; Preda, Adrian
<x content-type="archive" xml:space="preserve">Abstract</x> Objective/Introduction Lurasidone is an atypical antipsychotic medication approved for the treatment of schizophrenia over a dose range of 40–160 mg/day. This study examined D2 receptor occupancy and its association with clinical improvement and side effects in patients with schizophrenia or schizoaffective disorder following repeated doses of 80, 120, or 160 mg/day of lurasidone. Methods Twenty-five patients with The Diagnostic and Statistical Manual of Mental Disorders, 4th ed. (DSM-IV) diagnoses of schizophrenia or schizoaffective disorder were washed out of their antipsychotic medications (5 half-lives) and randomly assigned to 80, 120, or 160 mg/day of lurasidone. Subjects were imaged with 18F-fallypride at baseline and at steady-state lurasidone treatment to determine D2 receptor occupancy. Results Blood lurasidone concentration (plus major metabolite), but not dose, significantly correlated with D2 receptor occupancy. D2 receptor occupancy in several subcortical structures is associated with positive but not negative symptom improvement or the presence of movement symptoms. Discussion Blood concentrations greater than 70 ng/mL may be required to achieve a 65% occupancy level in subcortical areas. Intersubject blood concentrations at fixed dose were highly variable and may account for the lack of dose correlations. Conclusions Positron emission tomography (PET) occupancy data suggest that greater than 65% occupancy can be achieved across the dose range of 80–160 mg/day and that some patients require higher doses to achieve antipsychotic efficacy; this finding supports prior randomized clinical trial results.